Development of Refrigeration Simulation to Enhance Teaching and Learning for Commercial Refrigeration System - Yunus, Faizal Amin Nur; Mohd Nazri, Khairul Akmal; Rahim, Mohd Bekri; Razali, Nizamuddin; Abdul Rahman, Khairul Anuar; Rozali, Zulfadli (Research and Innovation in Technical and Vocational Education and Training, 2021)
The product is developed to ease and enhance teaching and learning session of teacher and students in DMC 4323 (Commercial Refrigeration System). The development of this product is to display the temperature and pressure of the refrigerator in smartphone by using Blynk application to perform Mollier Chart and reading of Coefficient of Performance (CoP). Temperature and pressure were detected by sensor and connected to Arduino Wemos board that was programmed by Arduino Ide. All the information was sent to cloud and can be access the server by using smartphone. Objectives of this product was to reduce high level of dependency on textbooks, enhance student’s ability to focus and improve several of teaching aids that moderate in quality.